Transitional justice, distributive justice, and transformative constitutionalism: comparing Colombia and South Africa - Bilchitz, David; Cachalia, Raisa; Correa Henao, Magdalena Ines; Bautista Pizarro, Nathalia (Oxford University Press, 2023)
Emerging from national pasts marred by violence, conflict, and injustice, South African and Colombian societies have sought to establish futures founded on equality, democracy, and constitutionalism. Transitional Justice, Distributive Justice, and Transformative Constitutionalism: Comparing Colombia and South Africa offers the first dedicated scholarly comparison of the two countries in relation to the intersecting ideas of transitional justice, distributive justice, and transformative constitutionalism. Featuring contributions by Colombian and South African authors, this volume richly examines each country from a range of thematic perspectives as the basis for deep reflection and comparison between them. Transitional Justice, Distributive Justice, and Transformative Constitutionalism brings together three interconnected concepts: the need for redress of past historical wrongs, the imperative to ensure fairness in the distribution of resources, and the commitment to law-governed social change mediated through a constitution. Part one explores innovative approaches to transitional justice that go beyond law, such as novel philosophical approaches to reconciliation, the use of art to address past wrongs, and the role of museums in memorialising the past. Part two considers one of the central components of transformative constitutionalism: socio-economic rights. It addresses the role of history in the interpretation of socio-economic rights and the procedural mechanisms that enable access to these rights. Part three looks at the development of legal structures designed to achieve both transitional and distributive justice in the areas of indigenous people's rights, procedural law, and international law.